REPAIR STRATEGIES IN TELEVISION TALK SHOWS: A CONVERSATION ANALYSIS - Rahayu, Gita (2016)
This study investigates the use of repair strategies used by Basuki Tjahaja Purnama (better known as Ahok) in two different talk shows: Mata Najwa, which is considered as a formal talk show, and Hitam Putih as an informal talk show. By employing qualitative method, this study examines repair strategies proposed by Schegloff, Jefferson, and Sacks (1977). This study uses one episode from each talk show which features Ahok as the guest. The focus of this study is the conversation among the participants (Ahok and the hosts) to see what types of repair strategies employed by Ahok and whether or not Ahok uses the same strategies in the two talk shows. The findings reveal three main points. First, there are three type of repairs used by Ahok in Mata Najwa and Hitam Putih: (1) self-initiated and self-repair, (2) other-initiated and self-repair, and (3) self-initiated and other-repair. Second, Ahok uses different repair strategies in each talk show. In this case, other-initiated and self-repair is the frequently repair strategies used in Mata Najwa and self-initiated and self-repair in Hitam Putih. Third, the format of the talk show has apparently influenced the use of repair by Ahok. Keywords: Conversation Analysis, Repair Strategies, Television Talk Shows. Penelitian ini meneliti penggunaan strategi repair yang digunakan oleh Basuki Tjahaja Purnama (lebih dikenal dengan sebutan Ahok) di dua jenis talk show: Mata Najwa, sebagai talk show formal dan Hitam Putih sebagai talk show informal. Dengan menggunakan metode kualitatif, studi ini membahas strategi repair yang dikemukakan oleh Schegloff, Jefferson dan Sacks (1977). Studi ini meneliti satu episode dari masing-masing talk show yang menghadirkan Ahok sebagai bintang tamu. Penelitian ini berfokus pada percakapan antara peserta talk show (Ahok dan pembawa acara) untuk melihat tipe repair apa saja yang digunakan oleh Ahok dan juga untuk melihat apakah Ahok menggunakan strategi yang sama di kedua talk show. Penemuan dari penelitian ini menghasilkan tiga hal utama. Pertama, ditemukan tiga tipe repair yang digunakan oleh Ahok di Mata Najwa dan Hitam Putih: (1) self-initiated dan self-repair, (2) other-initiated dan self-repair dan (3) self-initiated dan other-repair. Kedua, Ahok menggunakan strategi yang berbeda di setiap talk show. Dalam hal ini, other-initiated dan self-repair merupakan strategi yang paling sering digunakan di Mata Najwa dan self-initiated dan self-repair di Hitam Putih. Ketiga, format talk show mempengaruhi penggunaan strategi repair yang digunakan oleh Ahok. Kata kunci: Conversation Analysis, Strategi Repair, Televisi Talk Show.